A MODEL FOR ASSESSING SUITABILITY OF AIR CARGO HUB IN SOUTHEAST ASIA USING AHP AND TOPSIS - jantachalobon, nattapong (Journal of Applied Engineering Science, 2018)
This research aims to develop a model for evaluating the selection of air cargo hub in Southeast Asia. This is because there is no standard evaluation form for air cargo hub, and also to bring the factors that affect the air cargo hub to help improve the airports in Southeast Asia to become a hub for air freight in the future. To develop this research model. The factors which used as criteria for evaluation can divided two ways; factor can be counted are number and factor cannot be counted are number. The data obtained from interviews, questionnaire surveys, and statistics. Using Delphi technique and panel data linear regression model to determine the real factors of air cargo hub. The data for multi-criteria decision making are the guideline for creating the evaluation form by using the AHP method to help in weighting the importance of four main criterions; geographic criteria, economic criteria, operational criteria and other criteria. Two different decision-making methods; AHP and TOPSIS, were used to determine the significance and prioritization of air cargo hub. The result of this research can provide airports with useful references for operation management and formulation of development strategies.
Keywords: hubs; evaluation; criteria; assessment; air